Analisis Hubungan Antara Porositas Dengan Penyerapan Air - Dian Purnamawati Solin; Nugroho Utomo; Siti Zainab (KERN, 2019)
Soils is one of key of infrastructure and agriculture development. Therefore, it is necessary to identify the behavior of soil. In this paper, the relation between porosity and water absorption were identified by using laboratory test. Based on the results of laboratory testing, the porosity value of the soil in the coastal areas tends to be small, with the largest porosity value = 0.388. Meanwhile, for water absorption, the largest percentage of water that can be absorbed in the soil is 35,925. By using a linear mathematical model found a relationship between soil porosity with water absorption y = 204.91x-44.4 with a regression value R2 = 0.9954.